Finding the Number of Weak Homomorphisms of Paths - Tawatchai Pomsri; Wannasiri Wannasit; Sayan Panma (Journal of Mathematics)
Let G and H be graphs. A mapping f from VG to VH is called a weak homomorphism from G to H if fx=fy or fx,fy∈EH whenever x,y∈EG. In this paper, we provide an algorithm to determine the number of weak homomorphisms of paths.